(3GdHOhQ GdRGgQI aj GdbQGAGJ GdYTQ GdeJhGJQIs - (3GdfTGQ , SQGL GdOjf CHh MaU YeQ Hf bGSe Hf eMeO GdeUQj GdCfUGQj, GdfTGQ,J (B900 (3g` s ((3GdUGdMjI s)
(3ChdgG (B:s
(3jbhd YeQ GdGfUGQi Hf bGSe CMeO Gddg GdPi Yde GdEfSGf eGde jYde hHYO aEf HYV CUOGbGFi SCdfi Cf CLeY cJGHkG ai GdbQGAGJ GdYTQ hCf GPcQ cd eSFdI ai eMdgG s
(3BNQgG (B:s
(3jYbhH eGjI hLO hKeGfjI hSJhf hLgkG efgG CQHYI hKeGfhf hLgG efOQLI eY bGdhf hCQHYhf hKeGfhf efOQLI eY GdShSi Nda CQHYI ChLg efOQLI eY bGdhf hgPG BNQ eGJjSQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdejcQhajde Hg Jdas
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs